Power sharing, trickery and advice for the successful government of the viceroyalty of Peru in the sixteenth and seventeenth centuries - Suárez, Margarita (2024)
This article analyzes how distribution of power between peninsular institutions and the viceroys coexisted with the legal and informal channels that were established to accommodate the aspirations of various viceregal groups. Although the power of the viceroys and the elites had increased since the end of the 16th century, under the protection of buoyant mining production, the polysynodial system did not allow Peruvian elites to rise within it. This resulted in a system circumvented through tricks, advice, and even by evading laws and corrupting patronage, which would end up vitiating the system of gifts that had previously worked successfully and allowed the union of the Hispanic empire in the beginnings of modern Europe.